Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1016/j.nurt.2007.10.053
|View full text |Cite
|
Sign up to set email alerts
|

HD Unmet Clinical Research Needs: Perspective From the Pre-Manifest HD Population

Abstract: This activity has been planned and implemented in accordance with the Essential Areas and Policies of the Accreditation Council for Continuing Medical Education (ACCME) to provide continuing medical education for physicians. The University of Rochester School of Medicine and Dentistry designates this educational activity for a maximum of 4.75 credits in the AMA PRA Category 1 Credit™ system. Physicians should claim credit only commensurate with the extent of their participation in the activity. The Symposium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Likewise, a phase I study examining the safety and tolerability of phenylbutyrate in HD (PHEND-HD) has recently been completed (Clinical Trials identifier—NCT00212316). In this study, phenylbutyrate was found to be both safe and well tolerated in early symptomatic HD subjects taking 15 g daily, and levels leukocyte histone acetylation were measurable, indicating that HDAC inhibition was occurring in response to treatment (Moser et al 2008 ) A similar dose escalation/de-escalation study using sodium phenylbutyrate in HD patients agreed with the MTD of 15 g daily (Hogarth et al 2007 ), and at 12 g/daily was found to correct gene expression of a 12 gene biomarker set previously identified by this group (Borovecki et al 2005 ).…”
Section: Hdacs Er Stress and Pro-inflammatory Pathways In Hdmentioning
confidence: 78%
“…Likewise, a phase I study examining the safety and tolerability of phenylbutyrate in HD (PHEND-HD) has recently been completed (Clinical Trials identifier—NCT00212316). In this study, phenylbutyrate was found to be both safe and well tolerated in early symptomatic HD subjects taking 15 g daily, and levels leukocyte histone acetylation were measurable, indicating that HDAC inhibition was occurring in response to treatment (Moser et al 2008 ) A similar dose escalation/de-escalation study using sodium phenylbutyrate in HD patients agreed with the MTD of 15 g daily (Hogarth et al 2007 ), and at 12 g/daily was found to correct gene expression of a 12 gene biomarker set previously identified by this group (Borovecki et al 2005 ).…”
Section: Hdacs Er Stress and Pro-inflammatory Pathways In Hdmentioning
confidence: 78%